The Development of an Ethnoscience-Based Science Module at Eucalyptus Oil Refining in Buru Regency to Reduce Student Misconceptions - Muhammad Rizal Hardiansyah; Rahmiati Darwis; Nur Hikmah (Jurnal Penelitian Pendidikan IPA, 2025)
This research is based on the limited learning resources that students can use independently. This research aims to develop an ethnoscience-based science module on the process of refining eucalyptus oil to determine the feasibility, practicality, and effectiveness of the module in reducing student misconceptions. The method used was research and development R&D. The research data obtained was analyzed using percentage descriptions. The results of the science module feasibility test showed that the feasibility of the material obtained a score of 88% with very feasible criteria. The feasibility of the media obtained a score of 89% with very feasible criteria. Furthermore, the feasibility of language obtained a score of 80% with appropriate criteria. The practicality of the module was tested through analysis of student responses to the module developed and a practicality score of 87% was obtained with very good criteria. This means that the ethnoscience-based science module developed has very good practicality in terms of a) attractiveness of the module, b) ease of use, c) ease of understanding the contents of the module, d) completeness of the contents of the module, and e) conformity with character values ethnoscience. According to the results of the analysis of learning outcomes tests accompanied by the Certainty of Response Index, it shows that the level of student misconceptions has decreased by 34% accompanied by an increase in the level of student understanding of concepts by 37%, and students who do not understand concepts have decreased by 3%. This shows that the module developed is effective in reducing student misconceptions